Reality of Sinamot: Uncovering the Meaning of Interdependence and Reliability Behind the Sinamot Practice in Traditional Batak Weddings - Charlotte Aulia Putri; Whedy Prasetyo (Reviu Accounting, Business & Organizations, 2026)
Research Objectives - This study aims to analyze how the practice of sinamot in Batak traditional weddings reflects characteristics of interconnectedness and reliability through the processes of recognition, measurement, recording, and accountability. Method - The study employed an interpretive qualitative approach with a phenomenological focus. Primary data were collected through interviews and document analysis involving five informants a married couple, the parents of the bride and groom, and a traditional village chief and were analyzed using the Miles and Huberman model. Findings - The research findings indicate that the recognition of sinamot begins with the marhusip or marhori-hori dinding agreement; measurements are determined through contextual family negotiations, while record-keeping and accountability are conducted in a simple, informal manner based on social legitimacy. The information generated is highly relevant for customary decision-making, but its technical reliability is lower than that of formal accounting practices. Theoretical Implications - This study can contribute by applying accounting concepts within a sociocultural context as a means of implementing relevance and reliability. Furthermore, this study is also expected to serve as a reference for future research examining accounting practices within a sociocultural context regarding the recognition of financial and non-financial information. Research Novelty - This study expands the field of cultural accounting by positioning sinamot as a customary-based economic practice that balances interdependence and reliability in a culturally distinctive form.